Tumor Necrosis Factor and its Soluble Receptors as Potential Diagnostic Markers of Endometriosis. Issue 4 (October 2017) - Rocha, Ana L.; Vieira, Erica L.; Ferreira, Márcia C.; Teixeira, Antonio L.; Reis, Fernando M.
Introduction: Tumor necrosis factor (TNF) is a proinflammatory and angiogenic factor produced by activated macrophages. TNF acts through the cell membrane receptors TNFR1 and TNFR2, whose soluble forms play an important role in regulating TNF activity through competition with its receptors. The aim of this study was to evaluate whether TNF and/or its soluble receptors are useful to detect endometriosis in women undergoing laparoscopy for gynecological complains. Methods: This was a prospective, controlled, cross-sectional study including 75 consecutive women scheduled for gynecological laparoscopy due to chronic pelvic pain, infertility, or a pelvic image suggestive of endometrioma. Plasma TNF and soluble TNF receptors (sTNFR1 and sTNFR2) were measured by flow cytometry with the Cytometric Bead Array Human TH1/TH2 Kit (BD Biosciences). Results: Women ultimately proven to have endometriosis had lower preoperative plasma levels of sTNFR1 (median 81 pg/mL vs. 121 pg/mL, p<0.05), resulting in higher TNF/sTNFR1 ratios compared to those without endometriosis (0.055 vs. 0.033, p<0.05). Using the cut-off <108 pg/mL for plasma sTNFR1 to detect endometriosis in this setting, the sensitivity was 51.6% (95% confidence interval [CI], 35%-68%), the specificity was 75.0% (95% CI, 61%-85%) and the positive likelihood ratio was 2.1 (95% CI, 1.1-3.8). The area under the ROC curve was 0.647 (SE = 0.065; 95% CI, 0.519-0.774; p = 0.031). Conclusions: Plasma sTNFR1 levels are lower in symptomatic women with confirmed endometriosis compared to symptomatic women without endometriosis. The lower plasma sTNFR1 levels may increase the bioavailability of TNF, thereby contributing to the systemic low grade inflammation associated with endometriosis.